Extracellular Vesicles in Preeclampsia: Can Small Packages Carry a Big Punch?. Issue 4 (21st December 2022) - Hess, P.; Winn, V.
Abstract : ( Anesth Analg . 2022;134:710–712) Globally, 9%, 5%, and 1.2% of pregnancies are complicated by preeclampsia, developing preeclampsia, and eclampsia, respectively. These complicated pregnancies represent 8% to 16% of maternal pregnancy deaths in high-income countries. In addition, these medical conditions often result in persistent vascular dysfunction after delivery, increased risk of lifelong hypertension and cardiovascular disease, diabetes, stroke, renal failure, and a 40% increase in premature mortality for the mother. In the child, hypertensive disorders often result in preterm delivery and subsequent severe complications of prematurity. This article analyzes two primary possible causes for preeclampsia and their corresponding studies.